2002
DOI: 10.1093/carcin/23.7.1155
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective effects of garden cress (Lepidium sativum) and its constituents towards 2-amino-3-methyl-imidazo[4,5-f]quinoline (IQ)-induced genotoxic effects and colonic preneoplastic lesions

Abstract: The chemoprotective effect of garden cress (GC, Lepidium sativum) and its constituents, glucotropaeolin (GT) and benzylisothiocyanate (BITC), a breakdown product of GT, towards 2-amino-3-methyl-imidazo [4,5-f] quinoline (IQ)-induced genotoxic effects and colonic preneoplastic lesions was investigated in single cell gel electrophoresis (SCGE) assays and in aberrant crypt foci (ACF) experiments, respectively. Pretreatment of F344 rats with either fresh GC juice (0.8 ml), GT (150 mg/kg) or BITC (70 mg/kg) for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…The coordinated nature of induction of phase 2 enzymes was studied in detailed in Wistar rats with BITC. BITC (0.5% (w/w) in the diet for 2 weeks) increased liver and small intestinal GST, QR and UDP-glucuronyl transferase activities by 1.7-to 11-fold [37] . BITC also increased GSH levels in the esophagus and small bowel of ICR/Ha mice by 63%−75% [38] .…”
Section: Mechanism Of Anticarcinogenic Activitymentioning
confidence: 99%
“…The coordinated nature of induction of phase 2 enzymes was studied in detailed in Wistar rats with BITC. BITC (0.5% (w/w) in the diet for 2 weeks) increased liver and small intestinal GST, QR and UDP-glucuronyl transferase activities by 1.7-to 11-fold [37] . BITC also increased GSH levels in the esophagus and small bowel of ICR/Ha mice by 63%−75% [38] .…”
Section: Mechanism Of Anticarcinogenic Activitymentioning
confidence: 99%
“…An extracolonic increase in phase 2 enzyme activity could protect the colon from carcinogens by reducing the delivery of partiallyactivated compounds from the systemic circulation (Pool-Zobel, 1999). Kassie et al (2002Kassie et al ( , 2003a have shown that in rodents exposed to the heterocyclic amine 2-amino-3-methylimidazo[4,5-f ]quinoline (IQ) the ability of juices prepared from cruciferous vegetables to protect against the induction of aberrant crypt foci (ACF) is correlated with their ability to increase the activity of the phase 2 enzyme UDP-glucuronosyl transferase form 2 in the liver. Cruciferous vegetables may also exert their protective effects through a local induction of phase 2 enzymes in the large intestine.…”
Section: Modulation Of Xenobiotic-metabolising Enzymesmentioning
confidence: 99%
“…Other cruciferous vegetables have received relatively little attention. Single studies have found that garden cress (Lepidium sativum) juice and cruciferous seed meals and hulls are protective, whereas broccoli has been shown to have no effect (Barrett et al 1998;Rijken et al 1999;Kassie et al 2002). The latter finding of no protective effect of broccoli against azoxymethane-induced ACF is somewhat surprising because the breakdown products of glucobrassicin and glucoraphanin, the major GLS found in broccoli, have been shown to inhibit azoxymethaneinduced ACF Kim et al 2003).…”
Section: Cruciferous Vegetables and Experimental Colon Cancermentioning
confidence: 99%
“…ACF are believed to be the earliest morphological alterations during the development of colonic mucosal neoplasia (15)(16)(17) and are used extensively to identify modulators of colon carcinogenesis. Indeed, the morphological and molecular features of ACF support the contention that ACF are putative preneoplastic lesions that can serve as biomarkers of colon cancer (18,19).…”
Section: Introductionmentioning
confidence: 78%